2019
DOI: 10.1016/j.celrep.2019.09.071
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Profiling of Childhood Tumor Patient-Derived Xenograft Models to Enable Rational Clinical Trial Design

Abstract: SUMMARY Accelerating cures for children with cancer remains an immediate challenge as a result of extensive oncogenic heterogeneity between and within histologies, distinct molecular mechanisms evolving between diagnosis and relapsed disease, and limited therapeutic options. To systematically prioritize and rationally test novel agents in preclinical murine models, researchers within the Pediatric Preclinical Testing Consortium are continuously developing patient-derived xenografts (PDXs)—many of which are ref… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 132 publications
(124 citation statements)
references
References 84 publications
8
103
1
Order By: Relevance
“…The COS-33 cell line was subcultured for more than 50 passages without obvious changes in morphology or proliferative potential after cryopreservation and resuscitation. The cytological features of COS-33 cells in the grafted tumor are similar to those in the parental PDX tumor (Figure 8), and previous studies demonstrated that the PDX tumors accurately reflect the genetic and biologic characteristics of the tumor of origin [4,16]. Thus, COS-33 cells may constitute an excellent in vitro and in vivo model representative of the original tumor.…”
Section: Discussionsupporting
confidence: 61%
See 4 more Smart Citations
“…The COS-33 cell line was subcultured for more than 50 passages without obvious changes in morphology or proliferative potential after cryopreservation and resuscitation. The cytological features of COS-33 cells in the grafted tumor are similar to those in the parental PDX tumor (Figure 8), and previous studies demonstrated that the PDX tumors accurately reflect the genetic and biologic characteristics of the tumor of origin [4,16]. Thus, COS-33 cells may constitute an excellent in vitro and in vivo model representative of the original tumor.…”
Section: Discussionsupporting
confidence: 61%
“…mTOR is an intracellular serine/threonine kinase involved in the PI3K/AKT pathway, that indirectly regulates ribosomal translation of mRNA into proteins necessary for cell growth, cell cycle progression, and cell metabolism, making it an excellent target for cancer cells to hijack. Because of its demonstrable response to mTOR-targeted rapamycin monotherapy, the PDX OS-33 model has been frequently used in many studies to test new mTOR inhibitors (e. g. temsirolimus), and the activity of combinations of rapamycin with other anticancer agents such as cisplatin, bevacizumab, eribulin (against the tubulin binding agent), and R1507 (a fully human monoclonal antibody targeting IGF-1R) [4,[20][21][22][23][24]. In addition, it was used to test new drugs inhibiting other signaling pathways such as STAT3 [17,22].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations